Synthesis and characterization of new temperature-responsive nanocarriers based on POEOMA-b-PNVCL prepared using a combination of ATRP, RAFT and CuAAC. (August 2016) - Góis, Joana R.; Serra, Arménio C.; Coelho, Jorge F.J.
Graphical abstract: Highlights: Conjugation of polymers synthesized via SARA ATRP and RAFT polymerization. Facile synthesis of temperature responsive diblock copolymers by CuAAC reaction. Synthesis of well-defined POEOMA- b -PNVCL copolymers. POEOMA- b -PNVCL copolymers self-assemble and are able to entrap hydrophobic molecules. Abstract: Narrowly distributed diblock copolymers comprising a non-linear poly(ethylene glycol) (PEG) analogue and a biocompatible temperature-responsive block were successfully synthesized for the first time through a "click" coupling approach, using the copper catalyzed azide-alkyne [3+2] dipolar cycloaddition (CuAAC) reaction. The alkyne-terminated poly( N -vinyl caprolactam) (PNVCL) was obtained by reversible addition fragmentation chain transfer (RAFT) polymerization and the α-azide terminated poly(oligo(ethylene oxide) methyl ether methacrylate (N3 -POEOMA) was synthesized by supplemental activator and reducing agent (SARA) atom transfer radical polymerization (ATRP). The ensuing temperature-responsive POEOMA- b -PNVCL copolymers are hydrophilic but became amphiphilic at temperatures above the low critical solution temperature (LCST) of the PNVCL and self-assemble into organized nanostructures. The thermal induced self-assembly behavior of these block copolymers and its dependence on block composition and solution properties, were accessed by turbidimetry and dynamic light scattering (DLS) analysis. Faster heating rates promote the formation of smaller and more stable particles (Dh  ∼ 150–180) with narrow size particle distributions (PDI < 0.1). TEM results revealed the formation of spherical aggregates at 45 °C. The encapsulation of nile red (NR), a model hydrophobic drug, into the hydrophobic domain of the diblock copolymer nanostructures as well as its temperature-triggered release was demonstrated by fluorescence spectroscopy. A small drop of the solution temperature causes the disruption of the nanostructures and induces the fast release of the hydrophobic content.